Trust to Pay? Tax Morale and Trust in Africa - Kouame, Wilfried (World Bank, Washington, DC, 2019)
Although low tax morale hits developing countries hardest, little is known about its determinants in those countries. This paper examines the impact of trust in public institutions and the neighborhood on individual tax morale in four African countries: Algeria, Ghana, Morocco, and Nigeria. First, the paper provides theoretical foundations of such a relationship. Further, the paper uses the World Value Survey to estimate the effects of trust in public institutions and the neighborhood on individual tax morale. The identification strategy employs the instrumental variables method and relies on historical data on the slave trade and the literature on the cultural heritage of trust. The paper finds that trust in public institutions and the neighborhood are largely associated with tax morale in the African countries under consideration. The findings are robust to an alternative identification strategy, additional controls, and a falsification test.